A trustworthy web service composition method for ubiquitous computing. (2017) - Zhao, Shenghui; Chen, Guilin; Wang, Huibin; Chen, Haibao
Mobile users using smart mobile device have a considerable amount of requirements of services from mobile cloud or internet, due to its resource scarcity. It is a big challenge to select the services meeting users' all demands, as the user has both the demands of trust and lower cost. The existing methods (Hang and Singh, 2011; Wu et al., 2014) of trustworthy service composition cannot balance the profits between the service provider and consumer in mobile situation. First, we design a heuristic algorithm, called feasible allocation set generation (FASG), to reduce the complexity of generating feasible allocation sets. Second, to balance the profits between service providers and consumers, a service composition method, based on the social surplus maximisation, is put forward and the corresponding heuristic algorithm, called RCA_H, is also designed to find the optimal feasible solution in polynomial time. Experiment results show that the proposed RCA_H algorithm guarantees the profits of both sides, and obtains more trusted service and better facilitates service providers to provide trustworthy services to meet users' customised needs compared with another method (Oh et al., 2008) based on user utility maximisation.